Research on Hydraulics and River Dynamics - Hrissanthou, Vlassios (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes nine original contributions focused on river hydraulics. Four of these resulted from cooperation between universities from different countries: (a) Russia and Poland , (b) Taiwan and the USA , (c) Iran and Italy, and (d) India and Italy . The other contributions resulted from research carried out in universities from South Korea [5], Greece [6], China , and Japan .